CBMT-27. PROTEOMIC MAP OF GLIOMA BIOPSIES REVEALS FUNCTIONAL DEFECTS IN ENDOCYTOSIS. (5th November 2018) - Boulay, Jean-Louis; Ritz, Marie-Françoise; Hutter, Gregor; Tostado, Cristobal; Buser, Dominik; Spiess, Martin; Frank, Stephan; Jenö, Paul; Mariani, Luigi
Abstract: BACKGROUND: Decades of molecular genetic analyses have shown that gliomas accumulate genetic alterations that result in the enhanced activity of growth factor receptor tyrosine kinases (RTKs) and mediators of downstream pathways. Among them are gain-of-function of EGFR, PDGFR, PIK3CA or BRAF, and loss-of-function of PTEN or NF1, resulting in exacerbated proliferative responses. METHODS: We performed deep proteomic analysis of human gliomas of distinct genetic backgrounds, i.e. IDH, TERT statuses in combination with EGFR or PDGFRA amplification. RESULTS: Mass spectrometric analysis confirmed the R132H mutation in the IDH -mutant biopsies. Proteomic quantification not only revealed strikingly high levels of EGFR protein in biopsies carrying EGFR amplification when compared to control biopsies from white matter, but also overexpression of EGFR irrespective of EGFR copy number status, genetic background, tumor histology or grade. Furthermore, proteomic data and Western blot analysis showed a general decrease in the expression of core components of clathrin-mediated endocytosis, like adaptin (AP2), clathrin (CLT) and dynamin (DNM) in tumors of all genotypes, histology or grades. Functional binding assays in two primary cell lines yielded identical binding of transferrin to its receptor, even though one contained much reduced transferrin receptor levels. This clearly shows that reduced endocytosis leads to prolonged residence time of receptors on the plasma membrane. CONCLUSION: These three groups of proteins are indispensable for clathrin-mediated endocytosis and inactivation of growth factor receptors. Thus, loss of endocytosis proteins increases the availability of RTKs at the plasma membrane by prolonging growth factor signaling, leading to a selective advantage in tumorigenesis and progression. We are currently performing electron microscopy to visualize impaired clathrin vesicle formation in glioma cell lines and extending our uptake assay to RTKs like EGFR. Further, we are currently investigating on a general endocytosis gene shut down in gliomas by epigenetic silencing.